Crystal structure of [bis-tris(pyrazolyl)methanecobalt(II)] [chlorobis(η2-benzoato)-η1-benzoato-manganate(II)] hydrate, Co(C10H10N6)Mn(C7H 5O2)3Cl · H2O - Moubaraki, B. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures